ANALISIS KINERJA LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH PERIODE TAHUN 2009-2014 (Studi Kasus: Kabupaten Tolitoli, Sulawesi Tengah) - Susilo, Aris Joko; Erviantono, Tedi; S.Fil.,MA, Bandiyah (CITIZEN CHARTER, 2015)
ABSTRAK Â  Regional Parliamentâ€™s bad performances issue is one of problems which should be solved immediately in all regions. Settlement of the issue would have positive impacts to people society in the region, including District Tolitoli, where the Regional Parliament (DPRD) District Tolitoli drives the legislation function to creating innovative Local Regulation (Perda) that suitable with local conditions. Keywords: performance, legislation, Regional Parliament.